A new species of Choleoeimeria (Apicomplexa: Eimeriidae) from the lizard, Scincus hemprichii (Sauria: Scincidae) - Abdel-Baki, Abdel-Azeem S; Al-Quraishy, Saleh; Abdel-Haleem, Heba M (Folia parasitologica, 2013)
Four out of twenty (20%) specimens of the lizard Scincus hemprichii Wiegmann, collected in Saudi Arabia were infected with a previously undescribed species of Choleoeimeria. Oocysts of Choleoeimeria jazanensis sp. n. are cylindroidal, 26 x 15 microm, with a smooth bilayered wall and a shape index of 1.7. Oocyst residuum and micropyle are absent. Sporocysts are subspherical, 10 x 7 microm, with a shape index of 1.3. The Stieda body is absent. Sporozoites are banana-shaped, 10 x 3 microm, with one refractile body and enclosed the fine granulated sporocyst residuum. The endogenous development is confined to the gall bladder epithelium, with infected cells being displaced from the epithelium layer towards lumen. Mature meronts are subspherical and estimates to produce 9-12 merozoites. Microgamonts are spherical in shape with diameter of 13 microm. Macrogamonts are subspherical with a prominent nucleus in centre and wall-forming bodies at periphery.
Keywords: Animals; Saudská Arábie; Saudi Arabia; ještěři; Coccidiosis; zvířata; Lizards; kokcidióza; Eimeriidae